(untitled) (The Planet, 2024)
Introduction: Septicemia is a medical emergency that requires early diagnosis and proper treatment. Due to indiscriminate use of antibiotics in our country, in many cases of septicemia blood culture remains negative this creates a diagnostic challenge. These in turn affect management. Serum lactate as well as serum procalcitonin markers can be good options in this regard. This study will help us to find out the role of serum lactate and serum procalcitonin level as a marker of bacterial sepsis and will help to use antibiotic properly. Objectives: The main aim of this study was to find out serum lactate and serum procalcitonin as a biomarker of severe sepsis. Methods & Materials: It is an observational cross-sectional study was carried out the Medicine inpatient department and intensive care unit of Dhaka Medical College Hospital, Dhaka during September 2015 to February 2016. A total number of 40 patients were enrolled in this study. Statistical analyses of the results were be obtained by using window-based Microsoft Excel and Statistical Packages for Social Sciences (SPSS-24). Results: In this study, 52.5% of patients are between the ages of 51 – 65 years, with 25% falling between the ages of 36 – 50 years. The mean age was 49.67 ± 8.78 years. while, depending on gender, 32 (80%) were male while the remaining 8 (20%) were female. Among the 40 patients, 65% had diabetes mellitus as a co-morbidity. Other chronic diseases and immunosuppressive factors put the patients vulnerable to severe sepsis. The majority of the patients had a mix of disorders or risk factors. Conclusion: Serum procalcitonin (PCT) and lactate have been identified as two of the most promising indications of sepsis in critically sick patients. These markers can be used in conjunction with clinical signs and standard lab parameters that may indicate a severe infection at the time of ICU admission. serum PCT and lactate might be included to the routine work-up of critically sick patients who have a suspicion of sepsis, which could enhance patient treatment and enhancement diagnostic certainty.